1985
DOI: 10.1128/mcb.5.8.2104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sequences in the herpes simplex virus thymidine kinase gene required for efficient processing and polyadenylation.

Abstract: The herpes simplex virus (HSV) type 1 thymidine kinase gene (tk) was resected from its 3' end with BAL 31 exonuclease. Two sets of plasmids were isolated that lacked information distal to the two copies of the hexanucleotide 5'-AATAAA-3' located at the 3' end of the HSV tk gene. The presence of a simian virus 40 origin of DNA replication in each plasmid facilitated analysis of patterns of transcription in transfected Cos-1 monkey cells. Transcription analyses were performed with an Si nuclease protection assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…1). Two TG-rich regions, resembling the TG-rich sequence found downstream of the poly(A) addition site in vertebrate genes (Gil and Proudfoot 1984;Coles and Stacy 1985;Conway and Wickens 1985;Sadofsky et al 1985) and possibly in plant genes (Joshi 1987), are found 70 and 124 nucleotides upstream of the processing site. A third TG-rich region is located 32 nucleotides upstream of the processing site and consists of several tandem repeats of the sequence TTTGTA (Fig.…”
Section: Analysis Of the Primary Structure Of A 195-nucleotide Camv Fmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Two TG-rich regions, resembling the TG-rich sequence found downstream of the poly(A) addition site in vertebrate genes (Gil and Proudfoot 1984;Coles and Stacy 1985;Conway and Wickens 1985;Sadofsky et al 1985) and possibly in plant genes (Joshi 1987), are found 70 and 124 nucleotides upstream of the processing site. A third TG-rich region is located 32 nucleotides upstream of the processing site and consists of several tandem repeats of the sequence TTTGTA (Fig.…”
Section: Analysis Of the Primary Structure Of A 195-nucleotide Camv Fmentioning
confidence: 99%
“…In addition, a less well-conserved T-rich or TG-rich element, usually situated imiPresent address: Agriculture Canada Research Station, Vancouver, B.C., V6T 1X2 Canada. mediately downstream of the poly(A) addition site, is important for both reactions in vivo and in vitro (Gil and Proudfoot 1984;Coles and Stacy 1985;Conway and Wickens 1985;Hart et al 1985;McLauchlan et al 1985;Sadofsky et al 1985;Sperry and Berget 1986). Both the AATAAA and the downstream element are required for formation of the specific cleavage and polyadenylation complexes (Skolnik-David et al 1987;Gilmartin and Nevins 1989).…”
mentioning
confidence: 99%
“…Examination of many polyadenylation signals has shown that besides the conserved AAUAAA sequence, there are surrounding RNA sequences required for efficient utilization of the AAU-AAA as a polyadenylation signal. Downstream efficiency elements (DSEs) have been identified in many different viral systems (Gil andProudfoot 1984, 1987;McDevitt et al 1984McDevitt et al , 1986Sadofsky and Alwine 1984;Cole and Stacy 1985;Conway and Wickens 1985;Sadofsky et al 1985;Zhang and Cole 1987;Wilusz et al 1988;Wilusz and Shenk 1990) at distances from 5 to 60 nucleotides downstream of the poly(A) addition site. These 'Coiiesponding author. elements do not conform to a consensus sequence but are characterized as either U-rich or GU-rich.…”
mentioning
confidence: 99%
“…This cleavage-polyadenylation event is mediated through two cis-acting sequence elements: a highly conserved hexanucleotide, AAUAAA, located 5 to 30 bases upstream of the cleavage site (8,12,22,27,35,37), and a less conserved U-or GU-rich stretch located downstream of the cleavage site (6,7,10,17,19,20,28,30,31). The selective recognition of alternative polyadenylation sites may play a role in the posttranscriptional regulation of gene expression (reviewed in reference 14).…”
mentioning
confidence: 99%